Dampak Globalisasi Terhadap Pengaturan Tanggung Jawab Sosial Perusahaan BUMN - Tami Rusli (KEADILAN PROGRESIF, 2017)
Article 88 of Law Number 19 Year 2003 on State-Owned Enterprises which states "SOEs can set aside a portion of their net profit for the purposes of small business /co-operative development and community development around state enterprises". The problem in this research is how the impact of globalization of corporate social responsibility of SOEs ?. The method used in this research is using normative juridical approach. The results of this study prove that the practice of corporate social responsibility multinational impact on corporate social responsibility policy in the country where the company operates, including in Indonesia. Awareness raising of corporate social responsibility practices related to areas such as Human Rights, environmental protection, health and safety and anti-corruption. In addition, consumers and investors are showing increased interest in supporting responsible business practices and demanding more information about how companies deal with risks and opportunities related to social and environmental issues.